Prevalence and Factors Associated with Learning Difficulties among University Students in Sarawak, Malaysia - Md Mizanur, Rahman; Monique, Sapong Jan; Mohamad, Sharul; Raasiuen, Iyeer; Vaishnavi, - (Medsci Publications, 2024)
Background: University students must learn rapidly and handle complex academic concepts, making it cru-cial to understand the prevalence of learning difficulties in this population. This study determines the preva-lence and factors associated with learning difficulties among university students. Methods: This cross-sectional correlation study was conducted at Universiti Malaysia Sarawak and involved 546 undergraduate students using self-administered questionnaires. IBM SPSS version 28 was used for de-scriptive and multivariate analysis. Results: The most common difficulties were in expression (33.3%) and general study (34.0%). Age positively correlated with all difficulties, while gender effects were statistically insignificant (p>.05). A positive attitude significantly reduced reading, writing, and calculation difficulties (p<.001), whereas a negative attitude in-creased expression and general study difficulties (p<.001). Individual factors notably affected the expression and general study, teacher-related factors impacted reading, writing, and calculation, and environmental fac-tors increased difficulties across all domains (p<.001). Better previous academic performance was associated with fewer difficulties (p<.05). Conclusion: The study recommends strategies to improve student attitudes, address individual, teacher-related, and environmental factors, and promote academic performance. Future research should explore dif-ferent educational systems and the role of gender in learning difficulties.